Lost in transfer – tracing policy diffusion and norm-shaping in Tanzania-China relations - Georg Lammich (Global Policy, 2024)
This article examines the complexities of policy transfer between China and Tanzania, focussing on the influence of linguistic and cultural discrepancies. It explores how African governments, particularly Tanzania, interpret and adapt Chinese policy concepts to align with their domestic priorities. The study employs a multi-method approach, including interviews, document analysis and literature review, to investigate the dynamics of Sino-Tanzanian relations. Findings reveal that while China's development and security discourses resonate with African policymakers, the semantic nuances and historical contexts of Chinese terms often lead to divergent interpretations. Despite several initiatives from China to infuse policy concepts into Tanzanian discourse, including projects such as a party leadership school and party-to-party dialogues, there are to date no successful adaptations or transfers of Chinese macro-policy concepts to Tanzania. The research highlights the critical role of language and cultural context in policy transfer processes, challenging the traditional view of passive policy reception in the Global South. It contributes to the broader understanding of policy transfer, emphasising the need to recognise the dynamic interplay of language, culture and political agency in the process. The study concludes with recommendations for recognising and addressing the interpretive challenges in international policy transfers to enhance mutual understanding and cooperation.
Keywords: 320